Softball Catching Learning Model Development for High School Students - Eva Faridah; Rubiyatno Rubiyatno; Syahril Adam; Mikkey Anggara Suganda (AL-ISHLAH: Jurnal Pendidikan, 2021)
The study aims to create a softball throw and catch learning model for high school students. Based on the findings of observations and interviews, it is possible to conclude that students struggle with throwing and catching techniques on softball material. Physical education teachers face a challenge in providing appropriate learning methods due to a lack of variety in applying the learning model. The research and development (R D) method was used in this study, with six stages of development. The following data analysis techniques were used in this study: This study employs both quantitative and qualitative descriptive data analysis. Based on the findings of this study, ten throwing and catching learning models with various variations have been developed. The effectiveness test was performed with the T-test to determine the effectiveness of the developed product. The t-test value, tcount = 31,647, was then obtained. The value of ttable obtained with confidence level = 0.05, dk = (n-1) = 30 – 1 = 30 was 2.1098. As a result, tcount exceeds ttable (tcount = 31,647 ttable = 2,093). Based on the test criteria of tcount ttable at =0.05 dk = 17, the developed model is very effective for use, particularly at the high school level.